Risk factors for recurrent primary sclerosing cholangitis after liver transplantation - Ravikumar, Reena; Tsochatzis, Emmanuel; Jose, Sophie; Allison, Michael; Athale, Anuja; Creamer, Felicity; Gunson, Bridget; Iyer, Vikram; Madanur, Mansoor; Manas, Derek; Monaco, Andrea; Mirza, Darius; et al. (Journal of hepatology, 2015)
The association between primary sclerosing cholangitis (PSC) and inflammatory bowel disease (IBD) is well recognised. However, the relationship between IBD and recurrent PSC (rPSC) is less well understood. We assessed the prevalence of rPSC and analysed the factors associated with rPSC post-liver transplantation and its influence on graft and patient survival. This is a UK multicentre observational cohort study across six of the seven national liver transplant units. All patients undergoing a first liver transplant for PSC between January 1 1990 and December 31 2010 were included. Prospectively collected liver transplant data was obtained from NHSBT and colitis data was retrospectively collected from individual units. There were 679 (8.8%) first transplants for PSC. 347 patients (61.4%) had IBD, of which 306 (88.2%) had ulcerative colitis (UC). 81 (14.3%) patients developed rPSC and 37 (48.7%) of them developed graft failure from rPSC. Presence of UC post-liver transplant (HR=2.40, 95% CI 1.44–4.02) and younger age (HR=0.78, 95% CI 0.66–0.93) were the only factors significantly associated with rPSC. rPSC was associated with over a 4-fold increase in the risk of death (HR=4.71, 95% CI 3.39, 6.56) with 1, 5, and 10-year graft survival rates of 98%, 84%, and 56% respectively compared to 95%, 88%, and 72% in patients who did not develop rPSC. The presence of UC post-liver transplant is associated with a significantly increased risk of rPSC. Furthermore, the presence of rPSC increases the rate of graft failure and death, with higher re-transplantation rates.